Intersubjective contributions on the development of teachers' intrasubjectivity in a continuing teacher education program - Carvalho, Raquel Cristina Mendes de (2018)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão, Programa de Pós-Graduação em Inglês: Estudos Linguísticos e Literários, Florianópolis, 2018.